2022
DOI: 10.3390/ijms23116320
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PIK3CA Actionable Mutations in the Circulome: A Proof of Concept in Metastatic Breast Cancer

Abstract: The study of circulating cancer-derived components (circulome) is considered the new frontier of liquid biopsy. Despite the recognized role of circulome biomarkers, their comparative molecular profiling is not yet routine. In advanced breast cancer (BC), approximately 40% of hormone-receptor-positive, HER2-negative BC cases harbor druggable PIK3CA mutations suitable for combined alpelisib/fulvestrant treatment. This pilot study investigates PIK3CA mutations in circulating tumor DNA (ctDNA), tumor cells (CTCs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For instance, alterations in ERS1 (Estrogen Receptor 1) gene, which is associated to oestrogen resistance, has been found in circulating tumor DNA of a cohort of patients with breast cancer [89]. Women with advanced hormone-receptor-positive and HER2 negative breast cancer eligible for therapy with alpelisib (active in patients with PIK3CA mutations), exhibit in the circulome (specifically in cDNA, EV and circulating tumor cells) PIK3CA mutations, mirroring the genomic alterations found in the corresponding cancer tissue [90].…”
Section: Role Of Liquid Biopsy In Heredo-familiar Tumorsmentioning
confidence: 95%
“…For instance, alterations in ERS1 (Estrogen Receptor 1) gene, which is associated to oestrogen resistance, has been found in circulating tumor DNA of a cohort of patients with breast cancer [89]. Women with advanced hormone-receptor-positive and HER2 negative breast cancer eligible for therapy with alpelisib (active in patients with PIK3CA mutations), exhibit in the circulome (specifically in cDNA, EV and circulating tumor cells) PIK3CA mutations, mirroring the genomic alterations found in the corresponding cancer tissue [90].…”
Section: Role Of Liquid Biopsy In Heredo-familiar Tumorsmentioning
confidence: 95%
“…In the rapidly progressing field of genomics, the development and progression of novel assays based on the profiling of DNA isolated from non-/minimally invasive liquid biopsies, such as blood and blood derivatives, urine, sputum, milk, tear fluid, and other body fluids that contain tumor-derived DNA, may develop a high potential [ 133 ] and become more attractive in clinical applications [ 148 ]. The analysis of circulating tumor-derived components, known as the “tumor circulome”, is useful for assessing the clonal heterogeneity of tumors, unlike tissue biopsies [ 149 ], and is considered to be a new frontier of liquid biopsies [ 150 ]. The tumor circulome includes circulating tumor nucleic acids (ctNAs: ctDNA and ctRNA), circulating tumor cells (CTCs), tumor-derived extracellular vesicles (tdEVs), and tumor-educated platelets (TEPs) that can be used as cancer biomarkers [ 149 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%
“…Based on parallel sequencing and digital genomics techniques, cfDNA analyses in the blood of BC patients have become a promising biomarker in breast oncology [ 152 ]. Combined analyses of the PIK3CA mutational status in ctDNA, CTCs, and tdEVs using real-time PCRs (RT-PCR) and next generation sequencing (NGS) have shown that the targeting of these genes in HR+/HER2− metastatic BC has significant benefits after the occurrence of endocrine therapy resistance through the modulation of the PI3K/AKT/mTOR signaling pathway [ 150 ].…”
Section: Breast Cancer Investigation In the Multi-omics Eramentioning
confidence: 99%
“…[119,120] Numerous studies have leveraged CTCs to uncover novel actionable mutations in various cancer types in pre-treatment or during treatment. For instance, a study used CTCs to identify PIK3CA mutations in estrogen-receptor-positive breast cancer, suggesting potential benefit from PI3K inhibitors [121]. Another study identified EGFR mutations in NSCLC CTCs, which could guide targeted therapy with EGFR inhibitors [122].…”
mentioning
confidence: 99%